2021
DOI: 10.3390/molecules26103062
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Co(II), Ni(II), and Cu(II) Complexes Containing a Tridentate Sulfathiazole-Based (ONN) Schiff Base

Abstract: New Co(II), Ni(II), and Cu(II) complexes were synthesized with the Schiff base ligand obtained by the condensation of sulfathiazole with salicylaldehyde. Their characterization was performed by elemental analysis, molar conductance, spectroscopic techniques (IR, diffuse reflectance and UV–Vis–NIR), magnetic moments, thermal analysis, and calorimetry (thermogravimetry/derivative thermogravimetry/differential scanning calorimetry), while their morphological and crystal systems were explained on the basis of powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…However, the peak formation of the oxirane group at 833 cm -1 supports the expected structure [60]. The peaks at 3357 and 3269 cm -1 observed in MPO spectrum belong to the -SO 2 -N-H group [61][62][63]. The observation of 1367 and 1228 cm -1 asymmetric stretching peaks of -SO 2 confirms the binding [64].…”
Section: Ftir Spectrophotometersupporting
confidence: 53%
“…However, the peak formation of the oxirane group at 833 cm -1 supports the expected structure [60]. The peaks at 3357 and 3269 cm -1 observed in MPO spectrum belong to the -SO 2 -N-H group [61][62][63]. The observation of 1367 and 1228 cm -1 asymmetric stretching peaks of -SO 2 confirms the binding [64].…”
Section: Ftir Spectrophotometersupporting
confidence: 53%
“…Additionally, Tz-31 was reported with a tetragonally distorted octahedral geometry and was tested against some bacteria strains (E. coli, P. aeruginosa, S. aureus and B. subtilis) by the well diffusion method. Coordination resulted in excellent inhibition in bacteria (40-45 mm), while ligand showed moderate inhibition (30-35 mm) [96].…”
Section: Copper Complexes With Tridentate Thiazole Ligandsmentioning
confidence: 99%
“…The Cu complex showed 40, 45, 42 and 43 mm of zone of inhibition, Ni complex showed 33, 37, 36 and 37 mm of zone of inhibition and Co complex showed 35, 40, 37 and 38 mm of zone of inhibition against E. coli, S. aureus, B. subtilis and P. aeruginosa. 16 The results showed that the metal complexes were more efficient than the parent ligand (Figure 6). 17 To a hot magnetically stirred dioxane Schiff bases, Cu, Co, Ni and Zn salts were added and refluxed for 2 h. For Schiff base ligands and metal complexes, in vitro antibacterial activity was determined against bacterial strains namely E. coli, Shigella flexneri, P. aeruginosa and S. typhi and the antifungal activity was determined against fungal strains namely C. albicans, Candida glabrata, A. flavus, Fusarium solani and Microsporum canis,.…”
Section: Introductionmentioning
confidence: 98%